'Guid times wi the bad times': The meanings and experiences of befriending for people living alone with dementia. (January 2022) - Andrew, Jane; Wilkinson, Heather; Prior, Seamus
Befriending is a service in which volunteers provide companionship and support usually to people who are lonely or isolated. Such services are promoted in Scotland's national strategy to improve the lives of people with dementia, around a third of whom live alone. However, little is known about the perspectives of recipients. Taking a holistic qualitative case study approach, the aim of this research was to explore how people living alone with dementia experienced befriending and the contexts in which their befriending relationships were meaningful. Three people were visited on five separate occasions. Largely unstructured conversations allowed individuals to prioritise areas of importance to them within the broad topics of befriending, everyday life, social networks and biography. Participants also had the option of 'showing' how they spent their time with their befriender. Data were analysed using the voice-centred relational method. Three key messages emerged: befriending satisfied unmet needs and wishes for particular kinds of relationship; befriending was a facilitated friendship; and befriending was a human response to contingent and existential limitations.